2015
DOI: 10.1105/tpc.15.00228
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Annotation of Physcomitrella patens Small RNA Loci Reveals That the Heterochromatic Short Interfering RNA Pathway Is Largely Conserved in Land Plants

Abstract: Many plant small RNAs are sequence-specific negative regulators of target mRNAs and/or chromatin. In angiosperms, the two most abundant endogenous small RNA populations are usually 21-nucleotide microRNAs (miRNAs) and 24-nucleotide heterochromatic short interfering RNAs (siRNAs). Heterochromatic siRNAs are derived from repetitive regions and reinforce DNA methylation at targeted loci. The existence and extent of heterochromatic siRNAs in other land plant lineages has been unclear. Using small RNA-sequencing (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 56 publications
2
45
0
Order By: Relevance
“…However, a protein sequence of similar features from P. patens was identified and clustered out of both DCL1 clades (conventional and conifer-specific, Figure S11 and Figure 9), suggesting a potential common origin for all species for these shortened DCL-like sequences. This sequence corresponds to a short variant of DCL1 recently characterized in P. patens and identified as MINIMAL DICER-LIKE (mDCL) (Coruh et al 2015). This gene lacks the N-terminal helicase domain of DCL proteins, and has only PAZ and RNAseIII domains.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, a protein sequence of similar features from P. patens was identified and clustered out of both DCL1 clades (conventional and conifer-specific, Figure S11 and Figure 9), suggesting a potential common origin for all species for these shortened DCL-like sequences. This sequence corresponds to a short variant of DCL1 recently characterized in P. patens and identified as MINIMAL DICER-LIKE (mDCL) (Coruh et al 2015). This gene lacks the N-terminal helicase domain of DCL proteins, and has only PAZ and RNAseIII domains.…”
Section: Resultsmentioning
confidence: 93%
“…The mDCL is specifically required for 23-nt siRNA accumulation associated with genomic repetitive elements. Mutant analysis showed a dependence of this protein on DCL3 for generating the complete set of siRNAs (Coruh et al 2015). Phylogenetic resolution of this protein remained unclear, although it clustered with DCL1 sequences in spite of its association with siRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, homologs of key genes known to be responsible for hcsiRNA biogenesis and function in angiosperms clearly exist in diverse plant lineages (Zong et al, 2009;Banks et al, 2011;Huang et al, 2015;Wang and Ma, 2015;You et al, 2017). Reverse genetic analyses of these homologs, coupled with sRNA-seq analyses of the mutants, has shown that hc-siRNAs exist in the moss P. patens (Cho et al, 2008;Coruh et al, 2015), which implies that the pathway was most likely present in the last common ancestor of all land plants. Whether hc-siRNAs have been specifically lost in the conifers and/or ferns remains an open question, but the presence of high levels of 24 nt RNAs in specific tissues of the conifers Norway spruce (Picea abies) (Nystedt et al, 2013) and Japanese larch (Larix leptolepis) (Zhang et al, 2013) suggests that this may not be the case.…”
Section: Conservation Evolution and Annotations Of Endogenouse Sirnasmentioning
confidence: 99%
“…In this "de novo" scenario, occasional antisense transcripts could form double-stranded RNA by pairing with sense transcripts, which could trigger the production of small interfering RNAs (siRNAs) to target DRM2 for de novo methylation in gene bodies. Although mechanistically feasible, it is difficult to explain why gbM is absent from many nonangiosperm plants (such as the moss Physcomitrella patens) with functional RdDM and MET1 pathways (12).…”
mentioning
confidence: 99%